Two hands and a tale: When gestures benefit adult narrative comprehension. (August 2020) - Dargue, Nicole; Sweller, Naomi
Abstract: It is well established that observing and producing gesture by a learner can enhance comprehension of verbal messages, including narratives. What is less well understood, however, is under which conditions gestures benefit comprehension most. This study examined the role of gesture observation and production in adult narrative comprehension, through investigating whether gesture production moderates the effect of gesture observation. Crucially, observing typical gestures, but not atypical gestures, significantly benefited narrative comprehension. Furthermore, no significant benefit of producing gestures was found, and there was no evidence that gesture production moderated the differential effects of observing typical and atypical gestures on narrative comprehension. Overall, the current study not only provides evidence that iconic gestures can benefit adult narrative comprehension, but also highlights under which conditions gestures are likely to be of benefit. Highlights: Observing typical but not atypical gestures benefited narrative comprehension. Producing gestures did not significantly benefit narrative comprehension. Gesture production did not significantly moderate gesture observation's effects. This study highlights instances when gesture benefits narrative comprehension.